Emission load analysis of land transportation on urban roads in Jember regency, Indonesia (a case study of Sultan Agung Road) - Mulia Santi Dwi; Fildzah Cantika Almas; Rohman Abdur (E3S Web of Conferences, 2023)
Jember Regency is located in East Java with a population density of 2,536,729 people in 2020. The higher population in Jember will be proportional to the high transportation activity. This will cause problems regarding air pollution due to vehicle exhaust emissions in Jember Regency. The aims of this study are to estimate the annual emission load of air pollutants on a segment of Jember City's urban roads and to recommend emission reduction strategies. The selection of strategies is conducted by considering experts’ judgments through the Analytic Hierarchy Process (AHP). Sultan Agung Road in Jember City was the target of this study because it is a national road in the middle of a busy shopping area around it. The results of this study show that the emission burden generated from the land transportation sector on Sultan Agung Road in Jember Regency includes 177.486 tons of CO/year; 48.638 tons of HC/year; 9.481 tons of NO2/year; 2.534 tons of PM10/year; 1,245.15 tons of CO2 /year and 0.421 tons of SO2 /year. Three strategies recommended by the experts to reduce emissions are BRT (Bus Rapid Transit) Operational Development, The use of Solar Cells in Public Street Lighting, and Smart Driving.